2019
DOI: 10.1016/j.midw.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Caring for women making unconventional birth choices: A meta-ethnography exploring the views, attitudes, and experiences of midwives

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights Available research suggests midwives c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 39 publications
(82 reference statements)
2
47
0
1
Order By: Relevance
“…Midwives in the UK, as in many other countries, are a graduate profession and as such are regulated by the Nursing and Midwifery Council (NMC) which is turn is overseen by the Professional Standards Authority for Health and Social Care. At the point of registration, midwives are expected to have the necessary 'behaviors, knowledge and skills required to provide safe, effective, person-centered care and services' [22] (p. 7). Underpinning these behaviors, knowledge and skills is professionalism, defined by the NMC as being ' .…”
Section: The International Confederation Of Midwives (Icm) Define a Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Midwives in the UK, as in many other countries, are a graduate profession and as such are regulated by the Nursing and Midwifery Council (NMC) which is turn is overseen by the Professional Standards Authority for Health and Social Care. At the point of registration, midwives are expected to have the necessary 'behaviors, knowledge and skills required to provide safe, effective, person-centered care and services' [22] (p. 7). Underpinning these behaviors, knowledge and skills is professionalism, defined by the NMC as being ' .…”
Section: The International Confederation Of Midwives (Icm) Define a Mmentioning
confidence: 99%
“…. ' [22] (p. 6) A midwife's professionalism is demonstrated through being accountable, a leader, an advocate and being competent [23]. While it is postulated that Midwives are autonomous practitioners, it is clear that they work within a strict country specific legal, regulatory, professional and moral code of practice [24], are expected to follow best practice evidence based guidelines such as those of the National Institute for Health and Care Excellence (NICE) and work within their employer guidelines and policies.…”
Section: The International Confederation Of Midwives (Icm) Define a Mmentioning
confidence: 99%
“…In consonance with this, studies have documented the forms of D&AC childbearing women have experienced in healthcare facilities. The women in these studies reported that they were physically abused [19], psychologically abused [19], detained for non-payment of bills [20], examined without consent [21,22], discriminated against because of their social status [21,22], denied of their choice of birthing position because of facility-recommended guidelines [22][23][24], and subjected to iatrogenic procedures such as episiotomies, in some instances done without anaesthesia, and with improper pelvic examinations [25]. This D&AC, Sen, Reddy & Iyer [26] argued, is driven by socioeconomic inequalities and institutional structures and processes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from countries other than Africa exploring maternity care providers' views on D&AC have reported interesting findings [23]. From a meta-ethnographic study, it is evident that midwives in the United Kingdom (UK) were aware of childbearing women's rights to autonomy but were often faced with a dilemma when childbearing women make birth position choice outside recommended guidelines [23].…”
Section: Introductionmentioning
confidence: 99%
“…In consonance with this, studies have documented the forms of D&AC childbearing women 4 have experienced in healthcare facilities. The women in these studies reported that they were physically abused [19], psychologically abused [19], detained for non-payment of bills [20], examined without consent [21,22], discriminated against because of their social status [21,22], denied of their choice of birthing position because of facility-recommended guidelines [22][23][24], and subjected to iatrogenic procedures such as episiotomies, in some instances done without anaesthesia, and with improper pelvic examinations [25]. This D&AC, Sen, Reddy & Iyer [26] argued, is driven by socioeconomic inequalities and institutional structures and processes.…”
mentioning
confidence: 99%